Implementation of Sustainable Lighting Through Community Involvement to Support Clean and Affordable Energy in Puri Cikoneng Indah Housing, Bojongsoang District, Bandung Regency - Reza Rendian Septiawan; Ardiansyah Ramadhan; Ashri Dinimaharawati; Galang Adira Prayoga (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2026)
Background: Inadequate environmental lighting in residential areas can increase safety risks and reduce community comfort, particularly during nighttime activities. This community service program was conducted in the Puri Cikoneng Indah Residential Area to address limited public lighting through the implementation of a sustainable solar-powered lighting system. The program aimed to improve environmental safety, support clean energy utilization, and empower the local community in managing renewable energy technologies. Contribution: The contribution of this program lies in providing a renewable energy–based lighting solution that enhances nighttime visibility and security while increasing community awareness of clean energy practices. In addition, the activity serves as a practical and replicable model for neighborhood-scale renewable energy implementation. Method:  A community-based approach was employed by actively involving residents throughout all stages of the program. The implementation process included field surveys, identification of lighting needs, system design, socialization and technical education, installation of solar-powered lighting components, and monitoring and evaluation to ensure system functionality and sustainability. Results: The results showed that an integrated solar-powered lighting system was successfully installed and operated independently from the conventional electrical grid. The residential environment became brighter and safer at night, and residents demonstrated improved understanding of the basic operation and maintenance of solar energy systems. Conclusion: Overall, the program achieved its objectives by improving environmental safety, promoting clean energy adoption, and strengthening community participation, thereby contributing to sustainable development at the local level.